Research on the motion characteristic of elbow joint angle based on the sEMG of single muscle. Issue 1 (31st December 2016) - YuWei, Wei; HanWu, He
Abstract: As the number of patients caused the stroke increase, there are many therapies applied to rehabilitation, but they lack scientific theoretical basis guidance. In the process of treatment, the muscle force analysis, and the movement of information to predict muscle activity, they can provide a theoretical basis for the design of rehabilitation exercise; the treatment is more targeted and efficient. According to the characteristics of upper limb motion, this article establishes a reasonable and effective mathematical model, and uses the Hill muscle model to establish the simplified musculoskeletal model. The simulation model of human upper limb is used to establish with anybody software. The subjects have an experiment with the elbow joint flexion and extension, and use the electromyography collection device to collect the sEMG of biceps brachii and triceps brachii. And the motion information is processed to obtain the motion angle, angular velocity and angular acceleration. After preprocessing the sEMG, the wavelet decomposition and reconstruction is used to deal with the sEMG. The reconstructed signal is compared with the motion information, and finds the relationship between sEMG signals and elbow joint motion and muscle force. The experiment confirms the sEMG of biceps brachii can directly reflect the changes of muscle force. It is concluded that the sEMG of a single muscle can directly reflect the information of elbow joint flexion and extension.